Tumor microenvironment-responsive prodrug nanoplatform via co-self-assembly of photothermal agent and IDO inhibitor for enhanced tumor penetration and cancer immunotherapy. (June 2020) - Liu, Yijia; Lu, Yan; Zhu, Xianghui; Li, Chao; Yan, Mengmeng; Pan, Jie; Ma, Guilei
Abstract: Nanomedicine-based phototherapy in combination with immune checkpoint blockade therapy has been reported as a promising strategy for improved cancer immunotherapy. However, tumor penetration of nanomedicine into solid tumor is still an unresolved obstacle to an effective drug delivery, leading to limitations in their applications. Here, we developed a tumor microenvironment-responsive prodrug nanoplatform for efficient penetration and photo-immunotherapy of cancer. The prodrug nanoplatform is performed by integrating PEGylated indoleamine-2, 3-dioxygenase (IDO) inhibitor (Epacadostat) and photosensitizer (Indocyanine green, ICG) into a core-shell nanostructure via intermolecular interactions, which can transform into small dual-drug complexes (<40 nm) at tumor microenvironment. The resulting small dual-drug complexes could undergo caveolae-mediated endocytosis, enhance cellular uptake, directly kill tumor cells, in situ trigger antitumor immune response and modulate IDO-mediated immunosuppression. More significantly, the prodrug nanoplatform in combination with PD-L1 checkpoint blockade synergistically promoted the antitumor immunity and efficiently inhibited the growth of both primary and abscopal tumors. The present study provides a novel delivery strategy for nanoenabled phototherapy and IDO inhibition to combine PD-L1 checkpoint blockade for achieving more effective therapy of solid tumors. Graphical abstract: Image 1